Nitrogen and sulfur co-doped carbon nano-microspheres as well as preparation method and application thereof
Nitrogen-sulfur co-doped carbon nanospheres prepared by a one-step method using imidazole dinitrile amine salt ionic liquid and imidazole hydrogen sulfate ionic liquid solve the problems of insufficient interlayer spacing and random doping distribution in sodium-ion battery anode materials, achieving high capacity, long cycle life and large-scale production.
Patent Information
- Application Number
- CN202511653829.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-12
- Publication Date
- 2026-01-27
AI Technical Summary
Existing sodium-ion battery carbon anode materials have limited interlayer spacing, random heteroatom doping distribution, and complex processes, making them unsuitable for large-scale fabrication. This results in sodium-ion batteries having low reversible capacity, poor rate performance, and short cycle life.
Using imidazole dinitrile amine salt ionic liquid as nitrogen source and imidazole hydrogen sulfate ionic liquid as sulfur source, a nitrogen-rich core was prepared through a one-step hydrothermal reaction and pyrolysis method. Combined with soluble cobalt salt catalytic graphitization and ammonia etching, a core-shell structure with gradient interlayer spacing was formed, realizing co-doped carbon nanospheres with nitrogen-rich core and sulfur-rich shell.
This technology achieves high specific capacity, excellent rate performance, and long cycle life for sodium-ion battery anode materials, making them suitable for mass production and overcoming the problems of insufficient interlayer spacing, random doping distribution, and complex processes in existing technologies.
Smart Images

Figure CN121405071A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of sodium-ion battery anode material technology, specifically to a nitrogen-sulfur co-doped carbon nanosphere, its preparation method, and its application. Background Technology
[0002] Sodium-ion battery anode materials are a key component determining the battery's energy density, rate performance, and cycle life. They are similar to lithium-ion (Li...) + Compared to sodium ions (Na), + The radius is larger (1.02 Å vs 0.76 Å), while the interlayer spacing of traditional graphite is only 0.335 nm, making it unsuitable for Na... + Providing sufficient space for insertion / extraction results in low reversible capacity, poor rate performance, rapid capacity decay at low temperatures, and short cycle life. Therefore, developing carbon-based anode materials with high capacity, high rate capability, and long cycle life has become a core challenge for the practical application of sodium-ion batteries.
[0003] Existing technologies mainly revolve around three major strategies: "interlayer spacing expansion, heteroatom doping, and pore structure construction," but they still have significant shortcomings. First, interlayer spacing control: Patent CN119735199A uses solvothermal-catalytic crosslinking of coal tar pitch, which is carbonized at 900°C~1200°C to obtain hard carbon microspheres with "larger carbon interlayer spacing". The reversible capacity at 0.1A / g is about 300mAh / g; however, the capacity drops sharply to <150mAh / g at 5C rate, and the specific range of interlayer spacing control is not disclosed.
[0004] Second, heteroatom doping: Existing technologies generally use a "one-pot hydrothermal + co-pyrolysis" method to introduce heteroatoms, resulting in a random distribution of elements in the carbon framework, making it difficult to simultaneously achieve high conductivity and high active site density. Patent CN202311634069 uses corn cob as a carbon source and employs Fe... 3+ Fe-NS co-doped carbon spheres were prepared by hydrothermal pre-intercalation, potassium bicarbonate activation, and thiourea secondary doping. Although the coexistence of N, S, and Fe elements was achieved, TEM images showed no core-shell gradient, and interlayer spacing data were not disclosed. Electrochemical tests showed a specific capacity of approximately 180 mAh / g at 5C rate, and a capacity retention of approximately 75% after 500 cycles, indicating insufficient high-rate performance and cycling stability.
[0005] Thirdly, regarding the core-shell structure design: Patent CN109065895A prepares Fe-Co co-doped CN core-shell microspheres through a three-step coating-carbonization-acid washing process using "Fe3O4@PANI@ZIF-67". Its design purpose is for oxygen reduction electrocatalysis, not for sodium-ion battery anodes. Although this material possesses a core-shell morphology, the outer shell is a Co-NC framework, and the core is a hollow carbon sphere derived from Fe3O4. The doping elements are randomly distributed radially, and the interlayer spacing is not mentioned. Patent CN108539163A uses SiO2 as a template and polydopamine as a carbon source to prepare mesoporous hollow nitrogen-doped carbon / manganese dioxide composite microspheres through alkaline etching, but the process requires multiple coating-calcination steps, making it cumbersome.
[0006] In summary, existing technologies generally suffer from the following drawbacks: limited interlayer spacing (≤0.39nm), and inability to simultaneously accommodate Na+. + Rapid diffusion and structural stability; heteroatom doping is single and randomly distributed, making it difficult to achieve precise control of core-shell partitioning; complex process (multi-step template-etching-activation), not suitable for large-scale preparation. Summary of the Invention
[0007] To address the shortcomings of existing technologies, this invention provides a nitrogen-sulfur co-doped carbon nanosphere, its preparation method, and its applications. This invention uses an imidazolium dinitrile ionic liquid as the nitrogen source and a soluble iron salt as the catalyst. After mixing with the carbon source, carbonization and nitridation are completed in one step via hydrothermal reaction to obtain a nitrogen-rich core. Then, using an imidazolium hydrogen sulfate ionic liquid as the sulfur source and a soluble cobalt salt as the graphitization catalyst, the nitrogen-rich core is mixed with the imidazolium hydrogen sulfate ionic liquid, and then loaded with the soluble cobalt salt and subjected to high-temperature pyrolysis to achieve sulfur doping and Co-catalyzed graphitization, resulting in a core-shell structure. The precursor is used as an etchant and a secondary nitrogen source. Finally, mesoporous etching and shell nitriding are completed simultaneously through heat treatment to obtain nitrogen-sulfur co-doped carbon nanospheres. This invention improves conductivity by enriching the core with nitrogen doping, enhances sodium ion adsorption by enriching the shell with sulfur doping, and optimizes graphitization and defect density by Fe-Co bimetallic synergistic catalysis. This solves the problems of insufficient carbon anode interlayer spacing, random doping distribution, and poor structural stability in existing sodium-ion batteries. At the same time, the invention overcomes the defects of existing processes (multi-step template-etching-activation) and unsuitability for large-scale preparation by stepwise pyrolysis and bimetallic catalysis.
[0008] To achieve the above objectives, the technical solution adopted by the present invention is as follows: The first objective of this invention is to provide a method for preparing nitrogen-sulfur co-doped carbon nanospheres, comprising the following steps: S1. Using soluble iron salt as a catalyst and imidazole dinitrile amine salt ionic liquid as a nitrogen source, the carbon source, nitrogen source, and soluble iron salt are dissolved together in water and subjected to a hydrothermal reaction. During the hydrothermal reaction, the carbon source dehydrates and condenses to form an amorphous carbon skeleton; the -C≡N and imidazole rings in the imidazole dinitrile amine salt ionic liquid act as a nitrogen source, embedding into the amorphous carbon skeleton to form pyridine nitrogen (N-6) and graphitic nitrogen (NQ); simultaneously, the Fe in the soluble iron salt... 3+ It is reduced to Fe nanoparticles and in situ supported on an amorphous carbon framework, catalyzing the graphitization of the amorphous carbon framework (I D / I G =0.8) and stabilize nitrogen doping sites to complete carbonization-nitridation and obtain nitrogen-rich core; nitrogen content >10at.
[0009] S2. A nitrogen-rich core and an imidazole hydrogen sulfate ionic liquid are mixed to obtain a mixture. A soluble cobalt salt is used as a graphitization catalyst, loaded onto the surface of the mixture, and then pyrolyzed. During pyrolysis, sulfur doping and Co-catalyzed graphitization are achieved, resulting in a core-shell structure precursor with a nitrogen-rich core and a gradient interlayer shell composed of graphitized carbon and amorphous carbon. The mechanism of sulfur doping is that during the high-temperature pyrolysis of the imidazole hydrogen sulfate ionic liquid, its HSO4... - It decomposes and generates sulfur-containing gases (such as SO2 and H2S) and active sulfur species (such as S radicals). The active sulfur species react with the amorphous carbon skeleton and are doped through the following pathways: ① Sulfur atoms replace carbon atoms in the amorphous carbon skeleton to form CSC bonds (such as thiophene structures); ② Sulfur atoms preferentially adsorb at the edges or defect sites of carbon layers in the amorphous carbon skeleton to form -SH or -S- functional groups.
[0010] The mechanism of Co-catalyzed graphitization involves the decomposition of soluble cobalt salts (at 700℃~1500℃ in an inert atmosphere) into Co nanoparticles, which are uniformly dispersed in the carbon matrix of the amorphous carbon framework. The Co nanoparticles dissolve the amorphous carbon at high temperatures and subsequently precipitate as graphitized carbon, reducing the disorder of the carbon layers in the amorphous carbon framework (I0). D / I G (Reduces) and increases the degree of graphitization. Co nanoparticles catalyze the ordered arrangement of carbon layers in the amorphous carbon framework, while the steric hindrance effect of sulfur doping expands the local interlayer spacing (d). 002 (From 0.36nm to 0.43nm), forming a gradient structure.
[0011] Formation of gradient interlayer spacing: nitrogen-rich carbon layer (d 002The core (0.36 nm) is generated by the pyrolysis of soluble iron salt and imidazole dinitrile amine salt, with high nitrogen content providing a conductive framework. Co catalysis and sulfur doping work together to extend the interlayer spacing of the outer carbon layers to 0.43 nm, while simultaneously forming 2 nm–5 nm mesopores, promoting Na+... + Rapid spread.
[0012] S3. Using ammonia as an etchant and secondary nitrogen source, the core-shell structure precursor is heat-treated in an NH3 atmosphere. During the heat treatment, NH3 decomposes to generate H· and N·. H· reacts with the amorphous carbon skeleton to generate volatile CH4 and CO. CH4 and CO selectively etch the carbon layer of the amorphous carbon skeleton to form mesopores. Co nanoparticles catalyze NH3 to generate H· and N·. H· performs local etching of the core-shell structure precursor from the surface to the inside, forming mesopores with a decreasing pore size gradient (the interlayer spacing between the outer and outer shells expands from 0.36 nm to 0.43 nm). At the same time, N· embeds into the amorphous carbon skeleton to form pyridine nitrogen (N-6) and graphitic nitrogen (NQ). The residual imidazole hydrogen sulfate pyrolysis products (such as N / S-containing organic matter) further provide a nitrogen source for doping, resulting in nitrogen-sulfur co-doped carbon nanospheres.
[0013] Preferably, the carbon source is selected from glucose, sucrose, water-soluble starch, dextrin or citric acid.
[0014] Preferably, the mass ratio of carbon source, imidazole dinitrile ionic liquid to soluble iron salt is 1:1~5:0.03~0.3.
[0015] Preferably, the mass ratio of the nitrogen-rich core, the imidazole hydrogen sulfate ionic liquid, and the soluble cobalt salt is 1:0.8~1.5:0.19~0.26.
[0016] Preferably, the soluble iron salt is selected from ferric nitrate, ferric chloride, ferric sulfate, or ferric acetylacetone.
[0017] Preferably, the soluble cobalt salt is selected from cobalt acetate, cobalt nitrate, cobalt chloride, cobalt sulfate, or cobalt acetylacetonate.
[0018] Preferably, the ethanol solution of the soluble cobalt salt is loaded onto the mixture by atomization.
[0019] Preferably, the pyrolysis conditions are: pyrolysis at 850℃~1000℃ for 1h~4h in an inert atmosphere.
[0020] Preferably, the heat treatment conditions are: pyrolysis at 700℃~850℃ for 0.5h~2h.
[0021] Preferably, the imidazole dinitrile ionic liquid is selected from 1-ethyl-3-methylimidazole dinitrile amine salt, 1-butyl-3-methylimidazole dinitrile amine salt or 1-vinyl-3-methylimidazole dinitrile amine salt.
[0022] Preferably, the imidazole hydrogen sulfate ionic liquid is selected from 1-ethyl-3-methylimidazolium hydrogen sulfate, 1-butyl-3-methylimidazolium hydrogen sulfate, or 1-propyl-3-methylimidazolium hydrogen sulfate.
[0023] The second objective of this invention is to provide nitrogen-sulfur co-doped carbon nanospheres prepared by the above-described method, comprising a core, a shell, and transition metal sites; the core contains 10 at% to 15 at% nitrogen, exhibiting high graphitization and abundant defect sites; the shell contains 2 at% to 8 at% sulfur, with uniformly distributed 2 nm to 5 nm mesopores on its surface; the transition metal sites are Fe-Co bimetallic nanoparticles, which are in situ embedded at the interface between the core and the shell, serving as a synergistic catalytic center for graphitization and defects, and a Na+-co-co-bimetallic nanoparticle. + Adsorption active sites.
[0024] Preferably, the molar ratio of Fe to Co is 1:1 to 1.5. When the molar ratio of Fe to Co is 1:1 to 1.5, the synergistic effect of the two reaches its optimal level, which can balance graphitization and defect density and optimize sodium storage performance. When Fe is in excess, that is, when the molar ratio of Fe to Co is less than 1:1, excessive graphitization occurs, reducing defect density. When Co is in excess, that is, when the molar ratio of Fe to Co is greater than 1:1.5, excessive etching occurs, which destroys structural stability.
[0025] A third objective of this invention is to provide the application of the above-mentioned nitrogen-sulfur co-doped carbon nanospheres in the preparation of sodium-ion battery anode materials.
[0026] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. This invention provides a method for preparing nitrogen-sulfur co-doped carbon nanospheres. Using an imidazolium dinitrile amine salt ionic liquid as the nitrogen source, the carbon source, nitrogen source, and soluble iron salt are dissolved together in water and subjected to a hydrothermal reaction. The carbon source dehydrates and condenses to form an amorphous carbon framework; the nitrogen-containing structure in the nitrogen source is embedded into the amorphous carbon framework to form pyridine nitrogen and graphitic nitrogen; simultaneously, the Fe in the soluble iron salt... 3+ Fe nanoparticles are reduced to Fe nanoparticles and in-situ supported on an amorphous carbon framework, catalyzing the graphitization of the amorphous carbon framework to obtain a nitrogen-rich core. Using an imidazole hydrogen sulfate-based ionic liquid as a sulfur source, the nitrogen-rich core and the sulfur source are mixed to obtain a mixture. A soluble cobalt salt is then supported on the surface of the mixture and subjected to pyrolysis, releasing HSO4 from the sulfur source. -The active sulfur species generated from the decomposition form CSC bonds with the nitrogen-rich amorphous carbon skeleton or are adsorbed into the carbon layers of the amorphous carbon skeleton. Simultaneously, soluble cobalt salts decompose into Co nanoparticles, catalyzing the conversion of some amorphous carbon skeletons into graphitized carbon, forming a core-shell structure precursor with a gradient interlayer spacing. The core-shell structure precursor is then heat-treated in an NH3 atmosphere. The H· generated from the decomposition of NH3 reacts with the amorphous carbon skeleton in the core-shell structure precursor, and the generated CH4 and CO etch the amorphous carbon skeleton to form mesopores. At the same time, the Co nanoparticles catalyze the H· and N· generated from NH3. The H· locally etches the core-shell structure precursor to form mesopores with a reduced pore size gradient, and the N· embeds into the amorphous carbon skeleton to form pyridine nitrogen and graphitic nitrogen, resulting in nitrogen-sulfur co-doped carbon nanospheres. This invention overcomes the shortcomings of existing processes (multi-step template-etching-activation) by using stepwise pyrolysis and bimetallic catalysis, which are complex and unsuitable for large-scale preparation. The prepared nitrogen-sulfur co-doped carbon nanospheres have a core-shell partitioned doping structure and gradient-expanded interlayer spacing. The nitrogen-rich core enhances conductivity, while the sulfur-rich shell enhances sodium ion adsorption. Fe-Co bimetallic synergistic catalysis optimizes graphitization and defect density, solving the problems of insufficient interlayer spacing, random doping distribution, and poor structural stability of existing sodium-ion battery carbon anodes.
[0027] 2. This invention provides nitrogen-sulfur co-doped carbon nanospheres, comprising a core, a shell, and transition metal sites; the core is a nitrogen-rich doped carbon layer with an N content of 10 at%~15 at%, and a graphite interlayer spacing d. 002 It is 0.36nm, I D / I G The S content is 0.8, indicating a high degree of graphitization and abundant defect sites; the outer shell is a sulfur-rich doped carbon layer with a S content of 2 at%~8 at%, and the interlayer spacing d is [missing value]. 002 The nanometer diameter is 0.43 nm, with uniformly distributed mesopores of 2 nm to 5 nm on the surface; the transition metal sites are Fe-Co bimetallic nanoparticles embedded in situ at the core-shell interface, serving as a "graphitization-defect" synergistic catalytic center and Na... + Adsorption active sites. The nitrogen-sulfur co-doped carbon nanospheres of the present invention are novel carbon nanospheres that combine "interlayer spacing gradient expansion + core-shell partitioned heteroatom co-doping + bimetallic catalytic graphitization" to achieve high rate, long cycle and excellent low-temperature performance of sodium-ion batteries.
[0028] 3. When the nitrogen-sulfur co-doped carbon nanospheres of the present invention are used as a negative electrode material for sodium-ion batteries, the specific capacity at 0.1 A / g and 5 A / g reaches 325 mAh / g and 188 mAh / g, respectively, and the capacity retention rate is 91% after 1000 cycles, demonstrating excellent rate performance and cycle stability.
[0029] 4. The preparation process of this invention is green and efficient, requiring no template etching, and is suitable for large-scale production. Attached Figure Description
[0030] Figure 1 This is a TEM image of N / S-HCSs from Example 1.
[0031] Figure 2 The image shows the XRD pattern of N / S-HCSs in Example 1.
[0032] Figure 3 This is a comparison chart of the electrochemical performance of N / S-HCSs in Example 1 and HCSs in Comparative Example 1.
[0033] Figure 4 The image shows the Raman spectrum of N / S-HCSs from Example 1. Detailed Implementation
[0034] The technical solution of the present invention will be clearly and completely described below with reference to the data in the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0035] It should be noted that the technical terms used in this invention are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of this invention. Unless otherwise specified, all raw materials, reagents, instruments and equipment used in the following embodiments of this invention can be purchased on the market or prepared by existing methods.
[0036] In existing technologies, the interlayer spacing extension is limited (≤0.39nm), which cannot simultaneously accommodate Na + Rapid diffusion and structural stability; heteroatom doping is single and randomly distributed, making it difficult to achieve precise control of core-shell partitioning; complex process (multi-step template-etching-activation), not suitable for large-scale preparation.
[0037] To address the problems existing in the prior art, this invention provides a method for preparing nitrogen-sulfur co-doped carbon nanospheres, comprising the following steps: using an imidazolium dinitrile amine salt ionic liquid as a nitrogen source, dissolving a carbon source, a nitrogen source, and a soluble iron salt together in water and carrying out a hydrothermal reaction; the carbon source dehydrates and condenses to form an amorphous carbon framework; the nitrogen-containing structure in the nitrogen source is embedded into the amorphous carbon framework to form pyridine nitrogen and graphitic nitrogen; simultaneously, the Fe in the soluble iron salt... 3+ Fe nanoparticles are reduced to Fe nanoparticles and in-situ supported on an amorphous carbon framework, catalyzing the graphitization of the amorphous carbon framework to obtain a nitrogen-rich core. Using an imidazole hydrogen sulfate-based ionic liquid as a sulfur source, the nitrogen-rich core and the sulfur source are mixed to obtain a mixture. A soluble cobalt salt is then supported on the surface of the mixture and subjected to pyrolysis, releasing HSO4 from the sulfur source. -The active sulfur species generated from the decomposition form CSC bonds with the nitrogen-rich amorphous carbon skeleton or are adsorbed into the carbon layers of the amorphous carbon skeleton. Simultaneously, soluble cobalt salts decompose into Co nanoparticles, catalyzing the conversion of some amorphous carbon skeletons into graphitized carbon, forming a core-shell structure precursor with a gradient interlayer spacing. The core-shell structure precursor is then heat-treated in an NH3 atmosphere. The H· generated from the decomposition of NH3 reacts with the amorphous carbon skeleton in the core-shell structure precursor, and the generated CH4 and CO etch the amorphous carbon skeleton to form mesopores. At the same time, the Co nanoparticles catalyze the H· and N· generated from NH3. The H· locally etches the core-shell structure precursor to form mesopores with a reduced pore size gradient, and the N· embeds into the amorphous carbon skeleton to form pyridine nitrogen and graphitic nitrogen, resulting in nitrogen-sulfur co-doped carbon nanospheres.
[0038] To address the insufficient interlayer spacing problem in the aforementioned existing technologies, this invention overcomes this problem by achieving a gradient interlayer spacing expansion from 0.36nm to 0.43nm through stepwise pyrolysis and Fe-Co bimetallic synergistic catalysis. To address the random doping distribution problem in the aforementioned existing technologies, this invention solves this problem through a core-shell partitioned doping strategy with a nitrogen-rich core and a sulfur-rich outer shell. To address the complexity and unsuitability for large-scale fabrication in the aforementioned existing technologies, this invention solves this problem through a template-free, one-step pyrolysis-in-situ doping-simultaneous etching green and efficient process.
[0039] To enable those skilled in the art to more clearly understand the technical solution of the present invention, the following will provide a detailed description in conjunction with specific embodiments: Example 1 A method for preparing nitrogen-sulfur co-doped carbon nanospheres, the preparation process flow is as follows: Figure 1 As shown, it includes the following steps: S1. Core fabrication: 1 g of glucose and 2 g of 1-ethyl-3-methylimidazolium dinitrate were dissolved in 50 mL of deionized water, and then 10 mL of 0.1 mol / L ferric nitrate solution was added. After stirring evenly, the mixture was transferred to a high-pressure reactor lined with polytetrafluoroethylene and hydrothermally reacted at 195 °C for 8 h. After the reaction was completed, the mixture was naturally cooled to room temperature and washed successively with anhydrous ethanol and ultrapure water. Then it was dried at 80 °C for 12 h to obtain nitrogen-rich cores, denoted as N-CMSs.
[0040] S2, Shell Growth: 1 g of N-CMSs was mixed with 1 g of 1-ethyl-3-methylimidazolium hydrogen sulfate to obtain a mixture. Then, 20 mL of 0.05 mol / L cobalt acetate ethanol solution was uniformly sprayed onto the surface of the mixture by continuous ultrasonic atomization. After spraying, the mixture was placed in a tube furnace and heated to 900 °C at 5 °C / min under a nitrogen atmosphere and held at that temperature for 3 h to achieve sulfur doping and Co-catalyzed graphitization, forming a gradient interlayer shell. After the reaction was completed, the mixture was naturally cooled to room temperature under a nitrogen protective atmosphere to obtain the core-shell structure precursor.
[0041] S3, mesoporous etching and secondary nitriding: The core-shell precursor was placed in a tube furnace and pyrolyzed at 800℃ for 1 h in an ammonia gas flow of 50 mL / min, simultaneously completing mesoporous etching and shell nitriding. After the reaction, it was cooled to room temperature under a nitrogen atmosphere to obtain nitrogen-sulfur co-doped carbon nanospheres, denoted as N / S-HCSs. The transmission electron microscopy (TEM) results are shown below. Figure 1 As shown.
[0042] Depend on Figure 1 The results show a clear core-shell boundary with no phase separation or aggregation, indicating the homogeneity of the hydrothermal-pyrolysis process. The interconnected mesoporous channels in the outer shell facilitate rapid diffusion of Na ions. In the core region, a highly graphitized carbon layer is observed (interlayer spacing d). 002 =0.36nm), corresponding to the nitrogen-rich doped region (N content >10at%), exhibiting a short-range ordered dense structure. In the outer shell region, a gradient-expanded carbon layer (d 002 =0.43nm), with uniformly distributed 2nm~5nm mesopores on the surface (formed by NH3 etching), corresponding to sulfur-rich doping (S content 2at%~8at%).
[0043] Figure 2 The results show that the nitrogen-sulfur co-doped carbon nanospheres prepared in Example 1 of this invention retain the graphite crystal structure, and their 002 diffraction peak is located at 26.5°, which is slightly shifted to a lower angle than that of standard graphite (~26.6°), indicating that the interlayer spacing is moderately expanded.
[0044] The Raman spectrum of the nitrogen-sulfur co-doped carbon nanospheres prepared in Example 1 of this invention is as follows: Figure 4 As shown, heteroatom doping introduces more defects. At approximately 1345 cm⁻¹ -1 and 1607cm -1 Two broad peaks appear at point I, corresponding to peak D and peak G respectively. D / I G The value is 0.8, where the intensity ratio of the D peak to the G peak in the Raman spectrum is denoted as I. D / I G .
[0045] Battery performance testing of the N / S-HCSs anode material was conducted using CR2025 coin cells. The anode was a sodium metal sheet, and the electrolyte was a 1 mol / L NaClO4 / EC:DEC (1:1) solution. Assembly was performed in a glove box filled with an inert atmosphere, and the assembled batteries were tested for charge-discharge performance using a Blue Battery testing system. Figure 3 As shown, N / S-HCSs achieved a specific capacity of 325 mAh / g at a current density of 0.1 A / g and 188 mAh / g at a current density of 5 A / g, with a capacity retention of 91% after 1000 cycles, demonstrating excellent rate performance and cycling stability.
[0046] Example 2 A method for preparing nitrogen-sulfur co-doped carbon nanospheres, the preparation process flow is as follows: Figure 1 As shown, it includes the following steps: S1. Core fabrication: 1.2 g of sucrose and 2.5 g of 1-butyl-3-methylimidazolium dinitrate were dissolved in 55 mL of deionized water, and then 12 mL of 0.08 mol / L ferric nitrate solution was added. After stirring evenly, the mixture was transferred to a high-pressure reactor lined with polytetrafluoroethylene and hydrothermally reacted at 180 °C for 10 h. After the reaction was completed, the mixture was naturally cooled to room temperature and washed successively with anhydrous ethanol and ultrapure water. Then it was dried at 70 °C for 14 h to obtain nitrogen-rich cores, denoted as N-CMSs.
[0047] S2, Shell Growth: 1 g of N-CMSs was mixed with 1.2 g of 1-butyl-3-methylimidazolium hydrogen sulfate to obtain a mixture. 25 mL of 0.03 mol / L cobalt acetate ethanol solution was uniformly sprayed onto the surface of the mixture by continuous ultrasonic atomization. After spraying, the mixture was placed in a tube furnace and heated to 850 °C at 4 °C / min under an argon atmosphere and held at that temperature for 4 h to achieve sulfur doping and Co-catalyzed graphitization, forming a gradient interlayer shell. After the reaction was completed, the mixture was naturally cooled to room temperature under an argon protective atmosphere to obtain the core-shell structure precursor.
[0048] S3, mesoporous etching and secondary nitriding: The core-shell precursor was placed in a tube furnace and pyrolyzed at 750 °C for 1.5 h in an ammonia gas flow of 40 mL / min, simultaneously completing mesoporous etching and shell nitriding. After the reaction was completed, it was cooled to room temperature under an argon atmosphere to obtain nitrogen-sulfur co-doped carbon nanospheres, denoted as N / S-HCSs.
[0049] Battery performance testing of the N / S-HCSs anode material was conducted using CR2025 coin cells. The anode was a sodium metal sheet, and the electrolyte was a 1 mol / L NaClO4 / EC:DEC (1:1) solution. Assembly was performed in a glove box filled with an inert atmosphere, and the assembled batteries were tested for charge-discharge performance using a Blue Battery testing system. Figure 3 As shown, N / S-HCSs achieved a specific capacity of 270 mAh / g at a current density of 0.1 A / g and 155 mAh / g at a current density of 5 A / g, with a capacity retention of 84% after 1000 cycles.
[0050] Example 3 A method for preparing nitrogen-sulfur co-doped carbon nanospheres, the preparation process flow is as follows: Figure 1 As shown, it includes the following steps: S1. Core fabrication: 0.8 g of water-soluble starch and 3 g of 1-vinyl-3-methylimidazolium dinitrate were dissolved in 45 mL of deionized water, and then 8 mL of 0.13 mol / L ferric nitrate solution was added. After stirring evenly, the mixture was transferred to a high-pressure reactor lined with polytetrafluoroethylene and hydrothermally reacted at 220 °C for 6 h. After the reaction was completed, the mixture was naturally cooled to room temperature and washed successively with anhydrous ethanol and ultrapure water. Then it was dried at 90 °C for 10 h to obtain nitrogen-rich cores, denoted as N-CMSs.
[0051] S2, Shell Growth: 1 g of N-CMSs was mixed with 0.8 g of 1-propyl-3-methylimidazolium hydrogen sulfate to obtain a mixture. 15 mL of 0.07 mol / L cobalt acetate ethanol solution was uniformly sprayed onto the surface of the mixture by continuous ultrasonic atomization. After spraying, the mixture was placed in a tube furnace and heated to 950 °C at 6 °C / min under a nitrogen atmosphere and held at that temperature for 2 h to achieve sulfur doping and Co-catalyzed graphitization, forming a gradient interlayer shell. After the reaction was completed, the mixture was naturally cooled to room temperature under a nitrogen protective atmosphere to obtain the core-shell structure precursor.
[0052] S3, mesoporous etching and secondary nitriding: The core-shell precursor was placed in a tube furnace and pyrolyzed at 850 °C for 0.5 h under an ammonia gas flow of 60 mL / min, simultaneously completing mesoporous etching and shell nitriding. After the reaction was completed, it was cooled to room temperature under a nitrogen atmosphere to obtain nitrogen-sulfur co-doped carbon nanospheres, denoted as N / S-HCSs.
[0053] Battery performance testing of the N / S-HCSs anode material was conducted using CR2025 coin cells. The anode was a sodium metal sheet, and the electrolyte was a 1 mol / L NaClO4 / EC:DEC (1:1) solution. Assembly was performed in a glove box filled with an inert atmosphere, and the assembled batteries were tested for charge-discharge performance using a Blue Battery testing system. Figure 3 As shown, N / S-HCSs achieved a specific capacity of 282 mAh / g at a current density of 0.1 A / g and 148 mAh / g at a current density of 5 A / g, with a capacity retention of 83% after 1000 cycles.
[0054] Example 4 A method for preparing nitrogen-sulfur co-doped carbon nanospheres (N / S-HCSs), the preparation process flow is as follows: Figure 1 As shown, it includes the following steps: S1. Core fabrication: 1.5 g of glucose and 1.8 g of 1-benzyl-3-methylimidazolium dinitrate were dissolved in 60 mL of deionized water. 15 mL of 0.05 mol / L ferric nitrate solution was added, and the mixture was stirred until homogeneous. The mixture was then transferred to a high-pressure reactor lined with polytetrafluoroethylene and subjected to hydrothermal reaction at 160 °C for 12 h. After the reaction was completed, the mixture was allowed to cool naturally to room temperature and washed successively with anhydrous ethanol and ultrapure water. The mixture was then dried at 75 °C for 16 h to obtain nitrogen-rich cores, denoted as N-CMSs.
[0055] S2, Shell Growth: 1 g of N-CMSs was mixed with 1.5 g of 1-hexyl-3-methylimidazolium hydrogen sulfate to obtain a mixture. 10 mL of 0.1 mol / L cobalt acetate ethanol solution was uniformly sprayed onto the surface of the mixture by continuous ultrasonic atomization. After spraying, the mixture was placed in a tube furnace and heated to 1000 °C at 3 °C / min under a nitrogen atmosphere and held at that temperature for 1 h to achieve sulfur doping and Co-catalyzed graphitization, forming a gradient interlayer shell. After the reaction was completed, the mixture was naturally cooled to room temperature under a nitrogen protective atmosphere to obtain the core-shell structure precursor.
[0056] S3, mesoporous etching and secondary nitriding: The core-shell precursor was placed in a tube furnace and pyrolyzed at 700°C for 2 hours in an ammonia gas flow of 30 mL / min, simultaneously completing mesoporous etching and shell nitriding. After the reaction was completed, it was cooled to room temperature in a nitrogen atmosphere to obtain nitrogen-sulfur co-doped carbon nanospheres, denoted as N / S-HCSs.
[0057] Battery performance testing of the N / S-HCSs anode material was conducted using CR2025 coin cells. The anode was a sodium metal sheet, and the electrolyte was a 1 mol / L NaClO4 / EC:DEC (1:1) solution. Assembly was performed in a glove box filled with an inert atmosphere, and the assembled batteries were tested for charge-discharge performance using a Blue Battery testing system. Figure 3 As shown, N / S-HCSs achieved a specific capacity of 293 mAh / g at a current density of 0.1 A / g and 155 mAh / g at a current density of 5 A / g, with a capacity retention of 87% after 1000 cycles.
[0058] Example 5 A method for preparing nitrogen-sulfur co-doped carbon nanospheres is the same as that in Example 1, except that the ethanol solution of 0.05 mol / L cobalt acetate in S2 is replaced with 10 mL instead of 20 mL, to obtain nitrogen-sulfur co-doped carbon nanospheres.
[0059] Example 6 A method for preparing nitrogen-sulfur co-doped carbon nanospheres is the same as that in Example 1, except that the ethanol solution of 0.05 mol / L cobalt acetate in S2 is replaced with 30 mL instead of 20 mL, to obtain nitrogen-sulfur co-doped carbon nanospheres.
[0060] Comparative Example 1 A carbon nanosphere, the preparation method of which is described in Example 1, includes the following steps: S1. Core fabrication: The core was obtained by dissolving 1g of glucose in 50mL of deionized water, without adding imidazole dinitrile amine salt or ferric nitrate, and then hydrothermally reacting it at 195℃ for 8 hours.
[0061] S2, Shell Growth: The precursor was obtained by mixing 1g of core microspheres with 1g of glucose, without adding imidazole hydrogen sulfate and cobalt acetate, and heating to 900℃ at 5℃ / min under a nitrogen atmosphere and holding for 3h.
[0062] S3, Mesoporous Etching: The product was pyrolyzed at 800℃ for 1 hour under a nitrogen atmosphere without ammonia etching to obtain carbon nanospheres, denoted as HCSs.
[0063] The battery performance of the HCSs anode material was tested under the same conditions as in Example 1. Figure 3 As shown, HCSs have a specific capacity of only 150 mAh / g at a current density of 0.1 A / g and a specific capacity of 80 mAh / g at a current density of 5 A / g, with a capacity retention of 65% after 1000 cycles.
[0064] The above results demonstrate that the present invention significantly improves the electrochemical performance of nitrogen-sulfur co-doped carbon nanospheres through nitrogen-sulfur co-doping and core-shell structure design.
[0065] It should be noted that when numerical ranges are involved in this invention, it should be understood that both endpoints of each numerical range, as well as any value between the two endpoints, can be selected. Since the steps and methods used are the same as in the embodiments, preferred embodiments are described here to avoid redundancy. Although preferred embodiments of the invention have been described, those skilled in the art, upon learning the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments as well as all changes and modifications falling within the scope of this invention.
Claims
1. A method for preparing nitrogen-sulfur co-doped carbon nanospheres, characterized in that, Includes the following steps: Using imidazolium dinitrile amine salt ionic liquid as the nitrogen source, a carbon source, a nitrogen source, and a soluble iron salt are dissolved together in water and subjected to a hydrothermal reaction. The carbon source dehydrates and condenses to form an amorphous carbon framework; the nitrogen-containing structures in the nitrogen source are embedded into the amorphous carbon framework to form pyridine nitrogen and graphitic nitrogen; simultaneously, the Fe in the soluble iron salt... 3+ The reduced Fe nanoparticles were in situ loaded onto an amorphous carbon framework, catalyzing the graphitization of the amorphous carbon framework to obtain a nitrogen-rich core. Using an imidazole hydrogen sulfate ionic liquid as the sulfur source, a nitrogen-rich core and the sulfur source were mixed to obtain a mixture. A soluble cobalt salt was then loaded onto the surface of the mixture and subjected to pyrolysis. The HSO4 in the sulfur source... - The active sulfur species generated by decomposition form CSC bonds with the nitrogen-rich amorphous carbon skeleton, or are adsorbed in the carbon layers of the amorphous carbon skeleton; at the same time, soluble cobalt salt decomposes into Co nanoparticles, catalyzing the conversion of some amorphous carbon skeletons into graphitized carbon, forming a core-shell structure precursor with a gradient interlayer spacing. The core-shell precursor was heat-treated in an NH3 atmosphere. The H· generated from the decomposition of NH3 reacted with the amorphous carbon skeleton in the core-shell precursor, and the generated CH4 and CO etched the amorphous carbon skeleton to form mesopores. At the same time, Co nanoparticles catalyzed the H· and N· generated from NH3. H· locally etched the core-shell precursor to form mesopores with reduced pore size gradient, and N· embedded in the amorphous carbon skeleton to form pyridine nitrogen and graphitic nitrogen, resulting in nitrogen-sulfur co-doped carbon nanospheres.
2. The method for preparing nitrogen-sulfur co-doped carbon nanospheres according to claim 1, characterized in that, The carbon source is selected from glucose, sucrose, water-soluble starch, dextrin or citric acid.
3. The method for preparing nitrogen-sulfur co-doped carbon nanospheres according to claim 1, characterized in that, The mass ratio of carbon source, imidazole dinitrile amine salt ionic liquid to soluble iron salt is 1:1~5:0.03~0.
3.
4. The method for preparing nitrogen-sulfur co-doped carbon nanospheres according to claim 1, characterized in that, The mass ratio of nitrogen-rich core, imidazole hydrogen sulfate ionic liquid to soluble cobalt salt is 1:0.8~1.5:0.19~0.
26.
5. The method for preparing nitrogen-sulfur co-doped carbon nanospheres according to claim 1, characterized in that, The pyrolysis conditions are: in an inert atmosphere, pyrolyze at 850℃~1000℃ for 1h~4h.
6. The method for preparing nitrogen-sulfur co-doped carbon nanospheres according to claim 1, characterized in that, The heat treatment conditions are: pyrolysis at 700℃~850℃ for 0.5h~2h.
7. The method for preparing nitrogen-sulfur co-doped carbon nanospheres according to claim 1, characterized in that, The hydrothermal reaction conditions are: hydrothermal reaction at 195℃~205℃ for 8h~10h.
8. A nitrogen-sulfur co-doped carbon nanosphere prepared by the preparation method according to any one of claims 1 to 7, characterized in that, Nitrogen-sulfur co-doped carbon nanospheres consist of a core, a shell, and transition metal sites. The nitrogen content in the core is 10 at% to 15 at%; The sulfur content in the shell is 2 at% to 8 at%, and the surface has uniformly distributed mesopores of 2 nm to 5 nm. The transition metal sites are Fe-Co bimetallic nanoparticles, which are in situ embedded at the interface between the core and the shell.
9. The nitrogen-sulfur co-doped carbon nanospheres according to claim 8, characterized in that, In Fe-Co bimetallic nanoparticles, the molar ratio of Fe to Co is 1:0.5~1.
5.
10. The application of the nitrogen-sulfur co-doped carbon nanospheres according to claim 8 in the preparation of sodium-ion battery anode materials.
Citation Information
Patent Citations
Preparation method of mesoporous hollow nitrogen doped carbon nanosphere / manganese dioxide zinc ion battery cathode material
CN108539163A
Preparation of Fe-Co co-doped carbon-nitrogen core-shell microspheres and its application in electrocatalysis
CN109065895A
Heteroatom-doped biomass carbon-based electrode material and preparation method and application thereof
CN117602611A